Hospital as an Object of Social Infrastructure in Yekaterinburg in 1723—1734 - A. M. Safronova; A. A. Safronov (Научный диалог)
For the first time, on the basis of published and archival documents, the issue of a hospital as an object of social infrastructure in early Yekaterinburg is considered. The relevance of the study is due to the fact that the literature contains only fragmentary information about the organization of medical services at state-owned factories in the Urals in the 1720s—1734s. It is noted that the main reason for this lies in the absence of a set of documents devoted to this topic, even at the level of one case, in their dispersion among voluminous cases with factory documentation. The efforts of the heads of the Ural factories V. N. Tatishchev and V. I. Gennin to hire a doctor from the center are revealed. Information about the construction of the first hospital in Yekaterinburg in 1723—1724 and 1727 is researched. Special attention is paid to the regulation of medical services for the population by the local administration and the implementation of Russian legislation in the field of medicine on the territory of the mining department in the Urals. The questions about the orderlies of the hospital, the organization of treatment of patients, their delivery to the hospital are considered; financing the work of the hospital, participation of the population and payment for food for the inpatients; keeping records of people in the hospital and money, spent on medical care. Special attention is paid to the methods of drug delivery to Yekaterinburg from St. Petersburg and Moscow, the preparation of medical students.